2020
DOI: 10.1590/1809-6891v21e-58211
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition in soybean silages with inoculant and molasses

Abstract: Chemical composition was assessed in soybean silages without any additive (control), with a microbial inoculant (I), with I + molasses (I+M), and with molasses only (M). Soybean plants were harvested at the reproductive 6 (R6) stage and ensiled in 2 kg-capacity PVC laboratory silos. The SIL ALL C4 inoculant produced by Alltech Brazil was used in combination with or without 2.5% molasses added to the natural matter base. A 4 × 6 factorial arrangement (4 additives × 6 fermentation periods) in a completely random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(16 reference statements)
0
1
0
2
Order By: Relevance
“…A viable alternative to deal with this problem is to manipulate the diet through the selection of forages of high nutritional quality, in terms of highly digestible protein and carbohydrates [11]. In this sense, maize (Zea mays L.), as a source of forage, provides fibrous carbohydrates and non-fibrous carbohydrates, such as water-soluble forms and starch [12][13][14], which is why it is considered to have high energy value for animal nutrition [15] and is used as a strategy to mitigate GHG emissions in ruminants, especially CH 4 [16,17]. In this regard, it has been shown that the silage of whole maize plants reduces the production of ruminal CH 4 [18] since the starch it contains promotes the formation of propionate and decreases the H 2 available to produce CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A viable alternative to deal with this problem is to manipulate the diet through the selection of forages of high nutritional quality, in terms of highly digestible protein and carbohydrates [11]. In this sense, maize (Zea mays L.), as a source of forage, provides fibrous carbohydrates and non-fibrous carbohydrates, such as water-soluble forms and starch [12][13][14], which is why it is considered to have high energy value for animal nutrition [15] and is used as a strategy to mitigate GHG emissions in ruminants, especially CH 4 [16,17]. In this regard, it has been shown that the silage of whole maize plants reduces the production of ruminal CH 4 [18] since the starch it contains promotes the formation of propionate and decreases the H 2 available to produce CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Os mecanismos para esses fenômenos, no entanto, ainda são incertos e só podem ser levantadas hipóteses de que fatores relacionados a um melhor fornecimento de nutrientes dietéticos ao duodeno, um aumento na síntese de proteína microbiana, uma reciclagem mais eficiente do nitrogênio disponível no rúmen e uma maior digestibilidade de nutrientes pós-rúmen. Rosa et al (2020) avaliaram a composição química em silagens de soja colhidas no estágio R6, com (I) ou sem (C) inoculante microbiano, com (M) ou sem melaço e interação (I + M) em 1, 3, 14, 28 e 56 dias após ensilagem. Os autores recomendam a adição de inoculante associado ou não ao melaço, por melhorar a composição química das silagens.…”
Section: Introdução Geralunclassified
“…Dessa forma, a busca pela redução da dependência de grãos, bem como dos custos de produção, o cultivo da soja planta-inteira para produção de silagem, destaca-se como alternativa. A soja apresenta rendimento satisfatório de matéria seca (9,3 a 11,3 t/ha) quando colhida nos estágios R5 ou R6 (Acikgoz et al, 2007), elevado teor proteico, alto valor energético, baixo teor de fibra e elevada digestibilidade da MS (Acikgoz et al, 2007;Rosa et al, 2020;De Morais et al, 2021). Além disso, é capaz de fixar nitrogênio atmosférico no solo e melhorar sua qualidade em sistemas de rotação de culturas (Ghizzi et al, 2020).…”
Section: Introductionunclassified